A Polymeric Nanobeacon for Monitoring the Fluctuation of Hydrogen Polysulfides during Fertilization and Embryonic Development. (19th February 2022) - Zhou, Yibo; Gu, Zhengxuan; Liu, Changhui; Yang, Sheng; Ma, Xiaofei; Chen, Qiaoshu; Lei, Yanli; Quan, Ke; Liu, Juewen; Qing, Zhihe; Yang, Ronghua
Abstract: Fertilization and early embryonic development as the beginning of a new life are key biological events. Hydrogen polysulfide (H2 S n ) plays important roles during physiological regulation, such as antioxidation‐protection. However, no report has studied in situ H2 S n fluctuation during early embryonic development because of the low abundance of H2 S n and inadequate sensitivity of probes. We herein construct a polymeric nanobeacon from a H2 S n ‐responsive polymer and fluorophores, which is capable of detecting H2 S n selectively and of signal amplification. Taking the zebrafish as a model, the polymeric nanobeacon revealed that the H2 S n level was significantly elevated after fertilization due to the activation of cell multiplication, suppressed partially during embryonic development, and finally kept steady up to zebrafish emergence. This strategy is generally accessible for biomarkers by altering the responsive unit and significant for facilitating biological analysis during life development. Abstract : The fluctuation of hydrogen polysulfide during the early embryonic development is revealed by a polymeric nanobeacon. A maximal level of H2 S n exists in the preliminary stage of embryogenesis, then the expression level of H2 S n was down‐regulated with the development of the embryo.